Challenges in the management of idiopathic pulmonary fibrosis from a low- and middle-income country - Chundrigar, Mohsin; Ali Khan, Adnan; Ansari, Shahreen; Awan, Muhammad Ozair; Zubairi, Ali Bin Sarwar (Journal of the Pakistan Medical Association, 2024)
Idiopathic pulmonary fibrosis (IPF) is the most common progressive form of interstitial lung disease (ILD) that leads to gradual deterioration of lung function and ultimately death. Data from low- and middle-income countries (LMIC) on IPF is scarce. In this communication, we report the challenges encountered in managing IPF from Pakistan’s largest tertiary care centre. A total of 108 patients with IPF were evaluated at the Aga Khan University Hospital in Karachi, Pakistan from January 2017 to March 2020. A significant concern was that most patients with IPF presented late during their disease. A bigger challenge encountered in clinical practice was the cost and non-availability of antifibrotic therapy in the country until mid-2020. Successfully addressing these limitations, it is anticipated that better care will be available for the patients suffering from IPF in this part of the world. Keywords: Interstitial Lung Disease, Pulmonary Fibrosis; Idiopathic Pulmonary Fibrosis, LMIC.